2020
DOI: 10.1007/s41042-020-00027-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Interventions for Teachers: a Randomised Placebo-Controlled Field Experiment Investigating the Effects of Workplace-Related Positive Activities

Abstract: A realistic-positive attitude has repeatedly been identified as an important protective factor against school teachers' stress and strain. However, effective programmes fostering teachers' positive emotions, thoughts, and behaviours are still lacking to date. Despite mounting evidence showing their effectiveness, positive psychological interventions have seldom been applied and studied in the work environment of teachers. While initial evidence highlights the potential value of positive interventions for teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
6
10
0
6
Order By: Relevance
“… Taghvaienia and Alamdari (2020) demonstrated that the provision of a 10-week positive psychotherapy intervention (i.e., integrated activities to boost selected positive virtues including contentment, gratitude, forgiveness, positive emotions, and positive relationships) improved happiness, psychological well-being, and hope among retired teachers in Iran. Dreer (2020) implemented a 2-week positive psychological intervention with activities that were aimed to boost gratitude, kindness, meaning, optimism, and teacher strengths and reported enhanced engagement and job satisfaction among teachers in Germany ( Dreer, 2020 ). Given the predominance of studies in countries that are categorized as Western, educated, industrialized, rich, and democratic (WEIRD) settings and the sparse body of empirical evidence in Asian contexts ( Hendriks et al, 2019 ), more research is needed to offer evidence on the mental health benefits of positive psychological interventions among in-service teachers in non-WEIRD cultural contexts.…”
Section: Well-being Interventions For Teachersmentioning
confidence: 99%
See 4 more Smart Citations
“… Taghvaienia and Alamdari (2020) demonstrated that the provision of a 10-week positive psychotherapy intervention (i.e., integrated activities to boost selected positive virtues including contentment, gratitude, forgiveness, positive emotions, and positive relationships) improved happiness, psychological well-being, and hope among retired teachers in Iran. Dreer (2020) implemented a 2-week positive psychological intervention with activities that were aimed to boost gratitude, kindness, meaning, optimism, and teacher strengths and reported enhanced engagement and job satisfaction among teachers in Germany ( Dreer, 2020 ). Given the predominance of studies in countries that are categorized as Western, educated, industrialized, rich, and democratic (WEIRD) settings and the sparse body of empirical evidence in Asian contexts ( Hendriks et al, 2019 ), more research is needed to offer evidence on the mental health benefits of positive psychological interventions among in-service teachers in non-WEIRD cultural contexts.…”
Section: Well-being Interventions For Teachersmentioning
confidence: 99%
“…Clearly, there are gaps that remain unaddressed in prior literature on the applicability of positive psychological interventions among teachers in collectivist societies. First, despite the evidence regarding the mental health payoffs linked to implementing multicomponent positive psychological interventions with teachers, these studies were carried out in more individualistic countries, such as Iran ( Taghvaienia & Alamdari, 2020 ) and Germany ( Dreer, 2020 ). Given that previous studies have shown that the effects of specific happiness-increasing activities, such as recalling acts of kindness ( Shin et al, 2021 ) and gratitude ( Shin et al, 2020 ), differ in individualist and collectivist societies, it is questionable to generalize the psychological benefits of these interventions in various contexts.…”
Section: Well-being Interventions For Teachersmentioning
confidence: 99%
See 3 more Smart Citations